(3TQM GdETGQGJs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ef jSJMb GdMeO dPGJg aEf GdYbhd eJWGHbI hGdCdHGH eJhGabI Ydi Cf GdYde CaVd GdSYGOGJ s
(3BNQgG (B:s
(3hCf CjVG Ch Ujc jG CNj ai GdOjf hUGMHi ai WdH Gdjbjf Cf JYed HgPG GTQM dcKQI eG ajg ef GdMbGFb GdObjbI hGdeHGMK GdYejbI s
(3Ydjg Jedjc SfI (B859s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B94s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdadSaI hGdefWbs